Pengaruh Metode Student Teams Achievement Division Terhadap Keaktifan Belajar Siswa Pada Mata Pelajaran PAI - Marcella, Wylma; Ismatullah, Ade; Rosadi, Adi (JURNAL MANAJEMEN PENDIDIKAN, 2025)
THE INFLUENCE OF THE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) METHOD ON STUDENTS’ LEARNING ACTIVENESS IN ISLAMIC RELIGIOUS EDUCATIONThis study was motivated by the low level of students’ learning activeness in Islamic Religious Education (IRE) classes. Data from 2025 indicate that student participation was only 40%, involvement in group assignments was 52%, and engagement in individual tasks was 45%. This issue stems from the lack of variety in teaching methods and students’ low motivation. As a solution, the Student Teams Achievement Division (STAD) method was implemented, which is a cooperative learning model that emphasizes collaboration among students in small groups. This study employed a quantitative approach with a quasi-experimental design, specifically a pre-test and post-test control group design. The research subjects consisted of two seventh-grade classes, each comprising 20 students. The experimental class used the STAD method, while the control class used conventional methods. Data were collected through tests measuring students’ learning activeness before and after the treatment. The data were analyzed using normality, homogeneity, and Independent Samples T-Test with the aid of SPSS. The results showed an increase in the mean scores of learning activeness in both classes, with a higher increase in the experimental class. The mean pre-test score of the experimental class was 76.10, which increased to 87.00 in the post-test. Meanwhile, the control class increased from 75.75 to 83.90. The t-test results indicated a significance value (Sig. 2-tailed) of less than 0.05, which means there was a significant difference between the two groups. The average N-Gain score for the experimental class was 80.75%, while the control class achieved 79.68%; both fall into the high-effectiveness category, but STAD demonstrated superior results. It can be concluded that the STAD method is effective in improving students’ learning activeness. Students’ activeness increased through discussions, group collaboration, and individual responsibility within the groups. Besides its pedagogical relevance, this method also reflects Islamic values such as mutual assistance in goodness and collective responsibility. Therefore, the STAD method is recommended as an alternative approach to enhancing learning activeness in IRE instruction.